The comparison of traditional vascular risk factor between hemorrhagic and non-hemorrhagic stroke - Pinzon, Rizaldy Taslim; Sanyasi, Rosa De Lima Renita; Wijono, Andre Dharmawan (Asian Journal of Medical Sciences, 2017)
Background: Understanding about risk factors of stroke based on its pathology is very important. Previous study about the vascular risk factors in patients with stroke in Indonesia is very limited. Aims and Objective: Measure the comparison between traditional vascular risk factors in patients with hemorrhagic stroke and non-hemorrhagic (ischemic) stroke. Materials and Methods: This was a nested case-control study using secondary data from electronic medical record and electronic stroke registry of Bethesda Hospital Yogyakarta Indonesia. The stroke was diagnosed with standard way by well-trained neurologist and confirmed with CT Scan. The traditional risk factors were defined systematically. We used Dupont Power and Sample Size calculation software and StatCal EpiInfo software with significance level 0,05. Result: The data of 200 subjects consisted of 100 patients with hemorrhagic stroke and 100 patients with non-hemorrhagic stroke. Hypertension was main vascular risk factor in both Group but it was more common in hemorrhagic stroke (OR: 2,528, 95% CI: 0,069 ; 0,316, p < 0,002). Dyslipidemia was a protective factor against hemorrhagic stroke (OR: 0,147, 95% CI: 1,415 ; 4,516, p < 0,001). Diabetes was more common in ischemic stroke compared with hemorrhagic stroke (68% and 32%) respectively. Conclusion: Hypertension, dyslipidemia, and diabetes were modifiable traditional vascular risk factors which significantly had effect on stroke. Asian Journal of Medical Sciences Vol.8(6) 2017 5-8